Philosophy of Science on The Development of Palliative Nursing Practice in The Implementation of Long-Term Care for The Elderly: A Literature Review - Agustini, Ni Luh Putu Inca Buntari; Satriani, Ni Luh Adi; Dewi, Ni Putu Ayu Ratna; Yulistina, Putu Desi; Dewi, Putu Sundari; Putra, Putu Agus Sujana; Wijayanatha, I Putu Arya; Yudha, Gede Khrisna Eka (JURNAL INFO KESEHATAN, 2023)
As people gets older can increase health problems due to degenerative processes, thus requiring long-term care. Nurses as providers of palliative nursing care are based on nursing philosophy as a guide for acting and behaving in providing nursing care. Provide scientific information to nurses related to the role of philosophy of science in the development of palliative nursing practice that supports the implementation of long-term care in elderly. A literature review study, using various databases from Pubmed, Google Scholar, Science Direct and Research Gate. The inclusion criteria for searching for literature sources is the year of publication of the articles used starting from 2017 to 2022, in English, Indonesian and full articles. The search keywords are, nursing philosophy, nursing theory, palliative nursing, palliative care. Article selection was carried out using PRISMA and critical appraisal with a final total of 20 articles. The provision of palliative care to patients is carried out through a philosophical approach that emphasizes optimal quality of life and function, mitigates symptoms that cause sadness and promotes the values of care that focuses on comfort so as to reduce suffering and improve the quality of life of patients and families. Palliative nursing includes an understanding of the disease, pain management, and general symptoms, and follow-up care planning. Nurses are expected to make the philosophy of nursing as a basic of human as a holistic being in providing palliative nursing care.